Análisis y aplicación de indicadores financieros en Improquimsa periodo 2011 – 2012 - Ramírez Rodríguez, Teddy Fernando (2015)
The application of financial analysis will be directed to the administration of the company Improquimsa, valuable information for the assessment and measurement of financial management and taking corrective and appropriate management decisions for productive activities. It will also be of great help to those who have the need for the financial ratios of liquidity, solvency and profitability that allows them to make credit decisions and will meet the requirements of the Academic Regulations of the National University of Loja, to obtain the title of Engineer in Accounting and Auditing, CPA. Pursuant to objections raised proceeded to application of vertical financial analysis on the state of economic situation and the balance sheet to assess the proportion that each account in the financial statements, where it was learned that the company has a distribution of its equitable and according to the financial needs active , then the horizontal analysis in order to provide a comparative tool Improquimsa where different users allows them to plan and improve the current situation was conducted , financial indicators applied the same that were of great importance as it allowed the same liquidity measure that has good current sources; leverage ratios determined a moderate rate and profitability show that for every dollar has a profit of 0.13 cents. Finally we conclude that the analysis and application of financial indicators will allow Improquimsa making decisions regarding the capital structure of the company and will serve to correct any imbalances present or future investment decisions and financing decisions to buy or sell, or decisions daily management to improve the development of the company